Mucosal immunomodulation by the non-bacterial fraction of milk fermented by Lactobacillus helveticus R389 - Vinderola, Celso Gabriel (2007)
The health promoting effects ascribed to probiotic bacteria and fermented dairy products arise not only from bacteria themselves but also from metabolites derived from milk fermentation. Exopolysaccharides produced during milk fermentation and peptides derived from major milk proteins, when released during fermentation, are potential modulators of various regulatory processes in the body. The aim of this work was to increase the knowledge of the previously observed immunomodulating capacity of milk fermented by Lactobacillus helveticus R389 by the study of the mucosal immunomodulation exerted by the non-bacterial fraction of the milk fermented at a constant pH6 (NBFpH6). The effects on IL-6 production by small intestine epithelial cells, the profile of IgA+ and cytokine+ cells (IL-2, IL-6, IL-10, TNF-α and IFN-γ) induced in the gut lamina propria, and the levels of total and specific secretory IgA in the lumen of BALB/c mice that received NBFpH6 for 2, 5 or 7 days were examined. There was an increase in the number of IgA+, IL-10+, IL-2+ and IL-6+ cells after all feeding periods. Total S-IgA in the small intestine lumen increased in mice that received NBFpH6 for 2 days. However, no specific antibodies against NBFpH6 were detected. Feeding of NBFpH6 for 7 days significantly (P < 0.05) enhanced IL-6 secretion by small intestine epithelial cells. NBFpH6 induced a non-specific mucosal response that was down-regulated for protective immunity, enhancing IL-6 production by epithelial cells and IgA production in the small intestine. These events improve the immunological defenses at the intestinal level, increasing host protection against pathologies. Because mucosal immune responses induced by certain dietary antigens play a large part in the prevention of gastrointestinal diseases, the oral administration of a mucosal adjuvant such as NBFpH6 may positively affect the milieu of the intestinal lumen. The opportunity exists then to manipulate the constituents of the lumen of the intestine through dietary means, thereby enhancing the health condition of the host.